The African Youth Civic Movements and the Struggle for Peace: The Case of Balai Citoyen and Filimbi. (September 2019) - Kasanda, Albert
Can African youth be a sustainable resource for peace? Under which requirements can such a project be achieved? This questioning introduces the concern of this article which examines the current burgeoning of African youth from conceptual and qualitative perspectives. Thanks to the awakening of critical voices of African civil society, African youth are more than ever active in the political arena. They contributed, for example, to the fall of the Compaoré regime in October 2014. They closely follow the evolution of democracy in Senegal and create anxiety for the Congolese (DRC) over the mandate regime. Their commitment can be viewed as a search for peace as social cohesion. The paper explores two case studies: the Balai citoyen and Filimbi. It affirms that these youth platforms deal with issues that are intertwined between local challenges, global interactions and transnational conflicts. They can be viewed as peace builders.